Analisis Karakteristik Fenomena Pre-Breakdown Voltage Berbasis Pengujian pada Media Isolasi Minyak - Negara, I Made Yulistya; Fahmi, Daniar; Asfani, Dimas Anton; Cahyaningrum, Dwi Krisna (Majalah Ilmiah Teknologi Elektro; Vol 16 No 3 (2017): (September - December) Majalah Ilmiah Teknologi Elektro, 2018)
Pre-breakdown voltage is a phenomenon of dielectric breakdown affecting insulation’s performance. The faster pre-breakdown voltage of insulation, the more significant its dielectric degradation. In this paper, pre-breakdown voltage in oil insulation was investigated by using DC high voltage in laboratory scale. Under testing, the streamer development was recorded by using a high-resolution camera. The measured current was synchronized with an image that was picked up during the oil insulation testing. By this experiment, the characteristics of the current in phenomenon pre-breakdown voltage at oil insulation was studied. The results showed that the measured current of pre-breakdown phenomenon in oil insulation under 28 kV to 30 kV excitation voltage is in a range 100 mA - 150 mA.
Keywords: Isolasi cair; Karakteristik fenomena prebreakdwon voltage